Entoepidemiology of Chagas disease in northwest Sao Paulo and cytogenetic analysis of its main vector, Triatoma sordida (Hemiptera: Triatominae) - Silistino-Souza, R. [UNESP]; Alevi, K. C. C. [UNESP]; Castro, N. F. C. [UNESP]; Freitas, M. N. [UNESP]; Papa, M. D.; Scandar, S. A. S.; Bestetti, R. R.; Rosa, João Aristeu da [UNESP]; Azeredo-Oliveira, M. T. V. [UNESP] (Funpec-editora, 2013)
One century after the discovery of Chagas disease, it is still considered as a major health problem, causing more deaths in the Americas than any other parasitic disease. The northwest region of Sao Paulo, a macro-region that includes cities with a high-quality of life, has particularly high rates of Chagas disease. Therefore, this study aimed to assess the number of patients with Chagas disease, and to identify the triatomine fauna in the northwest region of Sao Paulo State, and to cytogenetically analyze Triatoma sordida mutants, thus providing new knowledge to control these species and avoid possible infections by Chagas disease. A total of 700 Chagas patients of both genders and variable age, who were born in and residents of the northwest region of the State of Sao Paulo were recruited for this study. Regarding the entoepidemiological fauna, both T. sordida and Rhodnius neglectus were captured from 2004 to 2011 in the northwest region of the Sao Paulo; however, T. sordida was the predominant species. Some of these collected triatomines were infected by Trypanosoma cruzi in several developmental stages. Furthermore, the lactoacetic orcein method was used for cytogenetic analysis. Several abnormalities were observed during meiosis of the T. sordida mutants, including condensed chromosomes with no chiasma, chromatin bridges between the autosomes, and some non-pairing homologous chromosomes. Thus, our study suggests that Chagas disease is currently not under control in Brazil. Furthermore, we suggest that cryptic speciation may be occurring in populations of T. sordida of Brazil. Further studies are necessary to understand the mechanisms behind these phenomena.
Keywords: Chagas disease; Entoepidemiology; Rhodnius neglectus; Mutants; Cryptic speciation